A few methods in charging fees for kafalah bank guarantee-i among Islamic banks in Malaysia - Syed Alwi, Sharifah Faigah; Ibrahim, Uzaimah; Md. Sawari, Mohd. Fuad (International Shari'ah Research Academy for Islamic Finance (ISRA), 2014)
Kafalah (guarantee) is generally considered as a tabarru' (gratuitous gift) act, and the majority of past Muslim jurists held the opinion that imposing ujrah (fee) on Kafalah is not allowed; however some contemporary jurists have allowed it. Islamic banks in Malaysia offer Bank Guarantee-i (BG-i) which uses the contract of Kafalah as the main contract, and they charge a fee for it. The objective of this paper is to determine the practice of Islamic banks in charging a fee for Kafalah BG-i and to get clarification from Islamic banks on the basis for their practices. The qualitative method is adopted as the main research methodology; the information on the practice of 12 Islamic banks in Malaysia is gained from semi-structured interviews conducted with bankers directly involved with Kafalah BG-i. This paper discovered that Islamic banks in Malaysia use three methods to determine the fee for Kafalah BG-i: using the percentage issued by the Association of Bankers Malaysia; calculating the actual cost incurred by the bank in issuing the BG-i; and using the bank’s own calculation or formula based on a percentage in determining the fee. There are two reasons for this variation. First, the Shariah Committees of Islamic banks have different interpretations of the nature of Kafalah: whether it is a tabarru' contract or aqd mu'awadah (contract of commercial exchange). Second, Bank Negara Malaysia (BNM) has not yet imposed any standard method upon Islamic banks for determining fees in Kafalah BG-i. BNM’s role is very important in recommending the best practice of charging fees among Islamic banks in order to avoid confusion among the bankers and the customers of Islamic banks regarding the most appropriate practice according to Shariah requirements.